Perluasan notasi Dewey Decimal Classification (DDC) tentang bahasa dan susastra Sunda - Rohman, Asep Saeful; Prijana, Prijana; CMS, Samson (Jurnal Kajian Informasi dan Perpustakaan, 2017)
The Sundanese language becomes one of the regional languages in the Indonesian Dewey Decimal Classification (DDC)âs notation 499.2232. The knowledge of Sunda has become a representation of the language used by the Sunda ethnicity in ancient and present times, thus it is necessary to record the development of language science and Sundanese literature into the DDC system in the library. This study aimed to extend the Deweyâs Classification notation in the field of the Sundanese language and literature. The scope of this study was to review the Indonesian and Sundanese language and literature notations in the 23rd edition of DDC Classification System, the development of knowledge about the Sundanese language and Sundanese literature, as well as the extension of the notation on the subjects. The research used a qualitative method using a descriptive. The result of this study was the extension of the Sundanese language and literature subject notation to complete the DDC classification scheme, which then would be submitted to the Library Material Development and Information Services in the National Library of Indonesia. Furthermore, the development of knowledge of the Sundanese language and literature that have been published in various forms of publication, to date can be represented by some more specific classification notation under the notation 499.223 2 for the Sundanese language and under notation 899.223 2 for the Sundanese literature. The notation will also provide benefits in the management of library materials as a representation of information contained in various publications on the Sundanese language and literature.